FEM analysis of wavelength effects in piezoelectric substrate - Abd Aziz, Norazreen (Institute of Electrical and Electronics Engineers Inc., 2014)
In this paper, we discussed simulation of several annular surface acoustic wave (A-SAW) devices using various wavelengths to identify its effects on the focusing properties and to analyze the propagation of Rayleigh waves in piezoelectric substrate. By choosing Y-cut Z propagating Lithium Niobate as the substrate and aluminum electrodes as the IDT, we modeled the A-SAW devices using Comsol Multiphysics. We used 8 pairs of annular electrodes with thickness of 1 μm with three different design's wavelength of 100 μm, 150 μm and 200 μm, respectively. To minimize the computational time in determining the optimum frequency i.e. resonant frequency of the device, only one pair of electrode for each design is simulated under eigenfrequency analysis in 2D piezoelectric (pzd) module. To understand the Rayleigh waves behavior, simulation of the whole device structure was done under frequency domain analysis in 2D-axisymmetric piezoelectric module. From the simulation results, it can be observed that SAW displacement profiles, electric potential field and operating frequency are significantly influenced by the wavelength. The formation of focused acoustic waves at the center of A-SAW device suits them in biosensing and microfluidic actuation applications that require detection or manipulation of localized variations.